Effects of dietary Fibrafid as phytogenic supplementation in standard and nutrient-reduced diets on breast meat quality, carcass traits, histopathology, and feed efficiency in heat-stressed broilers - Al-Garadi, Maged A.; Alhotan, Rashed A.; Hussein, Elsayed O.; Qaid, Mohammed M.; Suliman, Gamaleldin M.; Al-Badwi, Mohammed A.; Fazea, Esam H.; Olarinre, Isiaka O. (Frontiers in Veterinary Science, 2025)
IntroductionCombating heat stress (HS), increasing broiler productivity, and enhancing meat quality are the major priorities in hot climate areas. This study evaluated the effects of Fibrafid, a natural plant-derived product, compared to a commercial prebiotic (TURBO Grow), on meat quality, physicochemical characteristics, carcass features, jejunal histopathology, final average body weight (ABW), and feed conversion ratio (FCR) in heat-stressed broilers fed either a standard or reduced nutrient density diet (diet with a 5% drop in amino acid density and a 1.5% reduction in ME).MethodsA total of 576 Ross 308 broilers were allocated to eight treatments in a 2 × 4 factorial design, with two diet types (standard vs. reduced) and four additive treatments (none, Fibrafid 0.15%, Fibrafid 0.25%, and TURBO Grow 0.10%). Carcass yield, breast meat physicochemical traits, texture, and intestinal morphology were assessed at 35 days of age, as well as overall ABW and FCR.Results and discussionTwo-way ANOVA revealed that diet and additive exerted significant main effects on several traits, with some diet × additive interactions. Fibrafid at 0.25% improved water-holding capacity, reduced cooking loss, and increased myofibrillar fragmentation index, while both Fibrafid levels revealed a better gut environment, indicating improved nutrition absorption compared with controls. TURBO Grow supplementation showed intermediate benefits. Carcass weight, carcass yield, and Warner–Bratzler shear force remained unaffected by diet or additives. Reduced diets did not impair breast yield when supplemented with Fibrafid. In conclusion, these results indicate that Fibrafid at 0.25% enhanced meat quality, breast yield, and intestinal integrity in heat-stressed broilers across both dietary regimens, supporting its potential as a functional feed additive under challenging production conditions.